Evaluation of the New North Carolina Burn Registry. Issue 4 (July 2017) - Chrisco, Lori; Travers, Debbie; Grant, Ernest J.
Abstract : High-quality burn registries can facilitate best practices in burn treatment, patient education, and research. A new burn registry was designed and implemented at the North Carolina Jaycee Burn Center in June 2013. The primary goals for the design of the new North Carolina (NC) burn registry were to improve reporting to the American Burn Association's National Burn Repository while maintaining current functionality and preserving previously collected data. The objective of this evaluation was to review the literature for best practices in designing a disease registry, benchmark the design of the NC burn registry with the best practices identified in the literature, and compare data quality before and after implementation of the new NC burn registry. The NC burn registry was evaluated using six measurable elements identified from essential indicators of the Agency for Healthcare Research and Quality user's guide for design, implementation, analysis, interpretation, and quality evaluation of registries. These elements were achieving objectives, using literature to inform the choice of data elements, improving completeness of information, employing consistency checks, providing clear, operational definitions of outcomes and other data elements, and minimizing active data collection. Five of the six chosen essential elements were found to have been met during the evaluation of the new NC burn registry. One essential element, improving completeness of information, had mixed results. The new NC burn registry improved reporting to the National Burn Repository while maintaining current functionality and preserving previously collected data. Abstract : Supplemental Digital Content is available in the text.